1999
DOI: 10.1002/(sici)1096-9101(1999)25:1<43::aid-lsm6>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Laser skin resurfacing using a frequency doubled Nd:YAG laser after topical application of an exogenous chromophore

Abstract: Background and Objectives: Although laser skin resurfacing performed with CO 2 or Er:YAG lasers is efficient, side effects such as prolonged postoperative erythema, delayed healing, scarring, and pigmentation, have been reported. These side effects are due to skin characteristics but also to variations of the thermal effects associated with laser skin resurfacing. The study aimed to evaluate a new laser resurfacing method based on a previous topical application of an exogenous chromophore in order to have repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…1,2 Initially, the Q-switched Nd:YAG laser at 1064 nm, either alone or in combination with a carbon particle solution, was shown to induce some dermal remodeling. 3,4 Subsequently, vascular lasers, such as the PDL or pulsed 532-nm lasers were used, with minimal efficacy as discussed later. The use of these aforementioned lasers has been largely replaced by the longer wavelength infrared lasers, which more effectively target the mid dermis, resulting in more consistent mild improvement in rhytides.…”
Section: Nonablative Resurfacing Nonablative Laser Systemsmentioning
confidence: 99%
“…1,2 Initially, the Q-switched Nd:YAG laser at 1064 nm, either alone or in combination with a carbon particle solution, was shown to induce some dermal remodeling. 3,4 Subsequently, vascular lasers, such as the PDL or pulsed 532-nm lasers were used, with minimal efficacy as discussed later. The use of these aforementioned lasers has been largely replaced by the longer wavelength infrared lasers, which more effectively target the mid dermis, resulting in more consistent mild improvement in rhytides.…”
Section: Nonablative Resurfacing Nonablative Laser Systemsmentioning
confidence: 99%
“…These animals are covered by thin hair, which falls out through the fourth week, grows in by the seventh to ninth week, and falls out again thereafter (male rats). This skin model has been used already for evaluation of laser irradiation in vivo [13][14][15]. Thanks to the absence of hair during the period, quantification of superficial skin damage can be easily performed.…”
Section: Animal Modelmentioning
confidence: 99%
“…The use of topical chromophores have been studied in laser skin resurfacing applications to increase thermal ablative damage for improved resurfacing results. Sumain et al proposed the viability of carbon-based topical chromophores on skin with 532nm laser irradiance for increased laser light absorption and subsequent heat transfer to dermal tissue [8]. The results showed that the coagulation depth was dependant on laser dose, and it was claimed that the use of the carbon-based chromophores were effective.…”
Section: Topical Chromophoresmentioning
confidence: 99%